THE EFFECT OF TRADING PLACE STRATEGY ON READING COMPREHENSION AT EIGHT GRADE STUDENTS AT MADRASAH TSANAWIYAH MADINATUSSALAM SEI ROTAN - Putri Panjaitan, Silmy Anggita (BRIGHT VISION Journal of Language and Education, 2024)
This research was aimed to find out whether the students’ ability in reading comprehension who taught by trading place strategy is better than without trading place strategy. The method of this research was quantitative method with the experimental research. The population of this research was the eight grade student which is distributed into two classes totally 60 students. There were 30 students in experimental class and there were 30 students in the control class. The finding of this research shows that teaching reading comprehension by using trading place strategy is effective. The mean of experimental class from pre-test was 34.00 and post-test was 71.67. It was proved by tvalues (17.530) which is higher than ttable (1.671) in degree significance 5%. Furthermore, the hypothesis test that sign 2- tailed (p) was 0.00 while alpha (α) was 0.05 (0.00 < 0.005). It means that Ho was rejected and Ha was accepted. So, the students’ ability in reading comprehension who taught trading place strategy is better than without trading place strategy.